Limits on Public Provision of Private Goods: Reply and Further Analysis - Denzau, Arthur T.; MacKay, Robert J. (American Economic Review, 1980)
In a final section to our article in this Review, we pointed out problems that might arise in a democratic setting from attempts to provide publicly private goods that are easily exchangeable. In particular, we considered the case in which the political collectivity in question was a small part of a larger, open economy so that the publicly distributed good could be resold to individuals outside the collectivity. We then attempted to deduce the restrictions on the distribution of benefit shares and tax shares that were necessary for an equilibrium to involve public provision of the good at a finite level. In simplest terms, we argued that if, for example, the town of Blacksburg attempted to provide bread publicly and a majority of its citizen-voters faced tax prices less than the price at which they could export the good to the rest of the economy, then this majority coalition would support unbounded increases in the level of public provision of bread. The pursuit of these by the majority coalition would imply, of course, bankruptcy for the minority coalition. These types of problems, we argued, made it unlikely that easily exchangeable private goods would be publicly provided.' Robert Staaf and E. G. West (hereafter, S-W) have taken issue with this section of our paper on several grounds. First, they argue that even if the collectivity is a small part of an open economy, individuals would not vote for an unbounded amount of the private good to be publicly provided since this would exhaust individual and total community They seem to argue that a voter would not support a level of public provision if his implied tax bill exhausted his initial income. This clearly is not true for those voters with tax shares less than their benefit shares. These individuals would be perfectly willing to borrow to finance their tax bills since they earn significant arbitrage profits at the exchange stage. In essence, S-W assume that individuals cannot borrow even when they can so easily arbitrage between the domestic and outside market at a profit. Ruling out borrowing in this context is arbitrary and, of course, it is no surprise that it leads to a bounded solution. As a result, we find this criticism of our conclusion unconvincing. Staaf and West also assert that in an open-economy setting, public provision of a private good leads, through a sequence of voting, to convergence to income equality. In this case, they are not simply tinkering with our assumptions to generate different results; rather, they are making a serious logical error. They argue that since the outcome resulting from public provision of a private good with exchange within a period is equivalent to a certain income increase or decrease, the individual's income in the next period can be treated as if it actually were higher or lower by that amount. Alternatively put, they treat the individual's wealth at the exchange stage during one period as the relevant income or wealth variable for the beginning of the next period. This is simply incorrect. The value of an individual's wealth at the exchange stage, denoted w1, consists of his initial income or *University of Arizona and Virginia Polytechnic Institute and State University, respectively. We would like to thank Carolyn Weaver, Robert Tollison, and Geoffrey Brennan for their helpful comments. The research for this paper was supported by the National Science Foundation under Grant SOC76-22438. 'We went on to argue that public provision is more likely to involve those types of private commodities, such as services, for which price discrimination is feasible. Thus, the issue is not whether there will be public provision of private goods or not but rather what types of private goods are more likely to be provided publicly.